Gaya Bahasa Pada Lirik Lagu "Bertaut" Karya Nadin Amizah - Fadilatunisa, Dede (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The lyrics of “Bertaut” by Nadin Amizah feature various stylistic devices that enhance the emotional message and deep meaning of the work.This study aims to analyze the figurative language used in the lyrics of Bertaut, a song by Nadin Amizah. As a meaningful piece of musical art, the song contains various linguistic elements that effectively convey deep emotions to its listeners. The research employs a qualitative descriptive approach using content analysis methods to identify and interpret the figurative language within the lyrics. The findings reveal that Nadin Amizah utilizes a range of figurative language, including personification, metaphor, hyperbole, and repetition, to enhance the emotional tone and meaning of the lyrics. These stylistic elements not only beautify the lyrics but also depict the emotional bond between the writer and her mother, which serves as the central theme of the song. This study provides insights into how figurative language can be effectively utilized in musical works to convey messages and build emotional connections with listeners.